2011
DOI: 10.1088/0004-637x/729/2/119
|View full text |Cite
|
Sign up to set email alerts
|

The Black Hole Mass in M87 From Gemini/Nifs Adaptive Optics Observations

Abstract: We present the stellar kinematics in the central 2 ′′ of the luminous elliptical galaxy M87 (NGC 4486), using laser adaptive optics to feed the Gemini telescope integral-field spectrograph, NIFS. The velocity dispersion rises to 480 km s −1 at 0.2 ′′ . We combine these data with extensive stellar kinematics out to large radii to derive a blackhole mass equal to (6.6 ± 0.4) × 10 9 M ⊙ , using orbit-based axisymmetric models and including only the NIFS data in the central region. Including previously-reported gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
413
4
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 448 publications
(473 citation statements)
references
References 63 publications
46
413
4
2
Order By: Relevance
“…For this source, we found two reliable black hole mass measurements based on stellar and gas dynamics, respectively: log(M BH /M ) = 9.82 ± 0.03 (Gebhardt et al 2011) and log(M BH /M ) = 9.5 ± 0.1 (Walsh et al 2013). For the present analysis we adopt the more recent estimate from Walsh et al (2013).…”
Section: Smbh Masses and Corresponding Time Scalesmentioning
confidence: 76%
“…For this source, we found two reliable black hole mass measurements based on stellar and gas dynamics, respectively: log(M BH /M ) = 9.82 ± 0.03 (Gebhardt et al 2011) and log(M BH /M ) = 9.5 ± 0.1 (Walsh et al 2013). For the present analysis we adopt the more recent estimate from Walsh et al (2013).…”
Section: Smbh Masses and Corresponding Time Scalesmentioning
confidence: 76%
“…Based on the stellar or gas dynamics in the core, the mass of the M 87 central BH has been estimated as M BH = 3.2, 3.5, and 6.2 × 10 9 M (by Macchetto et al 1997;Gebhardt et al 2011;Walsh et al 2013, respectively). Here, we adopt the most recent value from the observations, M BH = 6.2 × 10 9 M , in all of our models.…”
Section: Scaling the Model To M 87 Corementioning
confidence: 99%
“…Owing to the uncertainty in the bulge effective radius for NGC 1271, we measure the effective stellar velocity dispersion ( e,bul s ) for three different bulge effective radii corresponding to the largest R e estimate from the Galfit decomposition, the smallest estimate of R e , and the average of the two. Additionally, some previous black hole studies have chosen to exclude data within r sphere when determining e,bul s because the stellar kinematics are under the direct influence of the black hole in this region (e.g., Gebhardt et al 2011;McConnell & Ma 2013 , which is the observed stellar velocity dispersion within a 3″. 5 aperture from the major-axis longslit data.…”
Section: Black Hole-host Galaxy Relationsmentioning
confidence: 99%
“…While recent progress has been made in searching for, and revising measurements for, black holes with masses larger than M 10 9  (Shen & Gebhardt 2010;Walsh et al 2010Walsh et al , 2013Gebhardt et al 2011;McConnell et al 2011McConnell et al , 2012van den Bosch et al 2012;Rusli et al 2013), many of these galaxies are giant ellipticals or brightest cluster galaxies (BCGs), which are often large (with R 10 e > kpc; e.g., Dalla Bontà et al 2009), have cored surface brightness profiles, and are dispersionsup-ported, showing little to no rotation. In contrast, the compact, high-dispersion galaxies found through the HET survey are small, are rapidly rotating, and generally exhibit cuspy surface brightness profiles.…”
Section: Introductionmentioning
confidence: 99%